LANDASAN PENGEMBANGAN KURIKULUM - Asep Nursobah; Mohamad Erihadiana; Andi Surya Abdi; Deden Sofwan Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Curriculum is the core of education where the curriculum can be interpreted as a set of plans and arrangements regarding objectives, content and learning materials as well as the methods used as guidelines for implementing learning activities to achieve certain educational goals. The basis for curriculum development can be interpreted as an idea, assumption or principle on which to rely. or starting point in developing a curriculum. The foundations for developing a curriculum include: religious foundations, philosophical foundations (perennialism, essentialism, existentialism, progressivism, reconstructivism), juridical foundations, psychological foundations, sociological or socio-cultural foundations and organizational foundations.